KOSMOLOGI RUANG ADAT SEBAGAI IDENTITAS PEMUKIMAN KAMPUNG NAGA, TASIKMALAYA - JAWA BARAT - Meta Khairunnisa (Diponegoro University, 2014)
[Title: Traditional Cosmologycal Space as Kampung Naga Setlement Identity, Tasikmalaya - Jawa Barat] Located far from the city, an architectural masterpiece grows and developes in traditional settlement. The form and settlement identity merges with emotional’s people inside that not only creates an identity but also influences in the development of surrounding area . local wisdom is created from local identity and cultural that becomes soul and character of the settlement (Haryanto,2007:89). Place is created by experience memories in the past that makes the familiar space and indepth meaning (Tuan,2010:73). Kampung Naga is one of the Sundanesse traditional settlement in West Java that maintains the culture and local wisdom, nevertheless globalisation begin to influences the meaning of cultural space inside. Its has a cosmology cocept, proper behaviour and religion that is created naturally and transmitted orally from generation to generation.The research is to understand cultural themes in Kampung Naga as an identity of Naga’s people. Etnography metodology is used to describe the space indepth and connectivity of the meaning. Cultural spaces that is created from cosmologycal persception and traditional low are Pamali space, Sacred Space and Gender space, the elements of space inside give indepth meaning and create local identity of Sundanese people.